2022
DOI: 10.1155/2022/1747822
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nanofiber Wearable Heart Rate Sensor Module for Human Motion Detection

Abstract: In order to further improve the detection performance of the wearable heart rate sensor for human physiological and biochemical signals and body kinematics performance, the wearable heart rate sensor module was optimized by using nanofibers. Nanoparticle-doped graphene films were prepared by adding nanoparticles to a graphene oxide solution. The prepared film was placed in toluene, and the nanoparticles were removed to complete the preparation of a graphene film with a porous microstructure. The graphene film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In recent years, there has been a rising demand for wearable sensors. Numerous types of research on sensors for physiological-signal monitoring have been reported, including motion of the body and muscles [2], heart rate (HR) [3], SpO 2 , body temperature [4], pulse, respiration, respiratory humidity [5], and electrophysiological signals (electrocardiogram (ECG), electromyogram (EMG), electrooculogram (EOG), etc.) [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a rising demand for wearable sensors. Numerous types of research on sensors for physiological-signal monitoring have been reported, including motion of the body and muscles [2], heart rate (HR) [3], SpO 2 , body temperature [4], pulse, respiration, respiratory humidity [5], and electrophysiological signals (electrocardiogram (ECG), electromyogram (EMG), electrooculogram (EOG), etc.) [6].…”
Section: Introductionmentioning
confidence: 99%